2018
DOI: 10.2139/ssrn.3186094
|View full text |Cite
|
Sign up to set email alerts
|

Is Socially Responsible Investing (SRI) in Stocks a Competitive Capital Investment? A Comparative Analysis Based on the Performance of Sustainable Stocks

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 94 publications
2
10
0
Order By: Relevance
“…Recently, socially responsible investing (SRI) has attracted increasing attention from researchers and investors (Blankenberg and Gottschalk, 2018; Pokorna, 2017; Rehman and Vo, 2020). The new generation of investing community and trade analysts emphasized issues beyond board characteristics and CEO compensation while understanding complexities associated with CG.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, socially responsible investing (SRI) has attracted increasing attention from researchers and investors (Blankenberg and Gottschalk, 2018; Pokorna, 2017; Rehman and Vo, 2020). The new generation of investing community and trade analysts emphasized issues beyond board characteristics and CEO compensation while understanding complexities associated with CG.…”
Section: Discussionmentioning
confidence: 99%
“…However, most later studies, such as those by Pedersen, Fitzgibbons, and Pomorski (2021), and Auer and Schuhmacher (2016), mainly found negative results. Interestingly, studies by Naffa and Hain (2018) and Blankenberg and Gottschalk (2018) reported a no-effect hypothesis.…”
Section: Literature Reviewmentioning
confidence: 98%
“…At the same time, empirical studies evaluating the performance of these sustainable investment approaches yield mixed return performance, which is problematic (Blankenberg & Gottschalk, 2018). However, most studies are limited by sample size, yet the sample period has been identified as a critical determinant in the financial performance of these sustainable investment strategies (Pokorna, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, portfolio investment emphasizes rational investment methods, rational investment concepts, state of health, and a stable investment market, which uses the expected value to represent the investment return and the standard deviation to represent the risk of return. [7] Thirdly and most importantly, increasing the variety and quantity of securities unrelated to each other in the portfolio can effectively reduce the risk of the whole portfolio. In that case, portfolio investment can easily solve the risk measurement of assets.…”
Section: Introductionmentioning
confidence: 99%